Molecular characterization of multidrug resistant Acinetobacter baumannii clinical isolates from Alexandria, Egypt - Sánchez-Urtaza, Sandra; Ocampo-Sosa, Alain; Molins-Bengoetxea, Ainhoa; El-Kholy, Mohammed A.; Hernandez, Marta; Abad, David; Shawky, Sherine M.; Alkorta, Itziar; Gallego, Lucia (Frontiers in Cellular and Infection Microbiology, 2023)
Carbapenem resistant Acinetobacter baumannii is a major global concern, especially in countries of the Middle East and North Africa, where the antibiotic resistance rates are on the rise. The aim of this study was to study the genomic characteristics and antimicrobial susceptibility profile of thirty-six multidrug resistant A. baumannii clinical isolates obtained in hospitals from Alexandria, Egypt. Antibiotic resistance rates were estimated by determination of Minimum Inhibitory Concentrations. Carbapenemase genes, other antibiotic resistance genes and virulence factors were then screened by the use of Whole Genome Sequencing. Isolates were also subjected to Multi Locus Sequence Typing (MLST) using the Pasteur Scheme and to core genome MLST to study their clonal relatedness. In addition, plasmid analysis was performed by the use of a commercial kit and S1- Pulsed Field Gel Electrophoresis, and Hybridization experiments with DIG-labeled DNA probes for blaNDM-1, blaPER-7 and blaGES-like were performed to locate these genes. The majority of isolates were resistant to β-lactams (including carbapenems), fluoroquinolones, aminoglycosides and trimethoprim; and some showed resistance to cefiderocol and minocycline. We identified 8 different blaOXA-51-like variants including blaOXA-51, blaOXA-64, blaOXA-65, blaOXA-66, blaOXA-68, blaOXA-91, blaOXA-94 and blaOXA-336; blaOXA-23, blaNDM-1, blaPER-7, blaGES-like and blaADC-like and other antibiotic resistance genes, some of these genes were within transposons or class 1 integrons. Multiple virulence factors responsible for adherence, biofilm production, type II and type VI secretion systems, exotoxins, exoenzymes, immune modulation and iron uptake were observed and 34 out of 36 isolates showed motility. Thirty-five out of 36 isolates clustered with International Clones 2, 4, 5, 7, 8 and 9; and 9 STs were identified including ST570, ST2, ST600, ST15, ST113, ST613, ST85, ST158, ST164. Plasmids ranging in size from 1.7 to 70 kb were found; blaNDM-1 and blaPER-7 genes were located in the chromosome and blaGES-like genes were simultaneously located in the chromosome and in a plasmid of 70kb. In conclusion, this study revealed a wide spectrum of antibiotic resistance genes and a variety of lineages among A. baumannii isolated in hospitals from Alexandria, and highlights the importance of investigating the molecular epidemiology to control the spread of multi-drug resistant isolates.